Encourage SMEs sustainable behavior during Covid-19 pandemic through competitive advantages and corporate culture - Zulfikar, Rizka Zulfikar; Widyanti, Rahmi Widyanti; Basuki, Basuki; Mayvita, Prihatini Ade; Purboyo, Purboyo (Serbian Journal of Management, 2021)
Several previous research had conducted to identify factors that have a significant impact on SMEs' sustainable behavior. But unfortunately, there has not been a single study that explores the influence of these factors in an ongoing pandemic condition. Our study tried to describe the level of effectiveness of the contribution and ability of competitive advantage factors and corporate culture in improving the SMEs sustainable behavior. The results of this study can be used for better SME development strategies, especially in conditions where pandemics such as COVID-19 are still ongoing. This research was conducted using a sample of 194 SMEs in the province of South Kalimantan-Indonesia. Sampling took by a purposive sampling technique and an online questionnaire as a research instrument. Data analysis techniques are using SEM by testing the construct validity and reliability, influence testing, path analysis, and contribution effectiveness analysis. This study found that competitive advantage had no significant effect on sustainable behavior, while corporate culture has a substantial impact on SMEs' sustainable behavior. The total direct impact and effectiveness of the contribution given by the corporate culture factor are more significant (79%) compared to the competitive advantage factor (21%).
Keywords: sustainable entrepreneurship; COVID-19; competitive advantages; corporate culture; SMEs